Enhancement the voltage clamp technique under noisy input currents - Khudhur, Ahmed Mahmood; Naif, Yasir Hashim; Khdher, Abdolbaqi Mohammed (LAP LAMBERT Academic Publishing, 2017)
Our brains keep working despite frequent failures of their component neurons, and this ‘fault-tolerant’ characteristic is of great interest to engineers who wish to make computers more reliable. Neuroscience is by far the most exciting branch of science because the brain is the most fascinating object in the universe. Every human brain is different - the brain makes each human unique and defines who he or she is.